PENGEMBANGAN ORGANISASI DAN PERWASITAN CABANG OLAHRAGA PETANQUE DI KABUPATEN INDRAMAYU - Yasep Setiakarnawijaya; Kuswahyudi (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract Indramayu Regency is 4 of 27 Regencies in West Java that does not yet have a Branch Committee of the Indonesian Petanque Sports Federation (FOPI) as the Organizing Commitee of the Petanque sports in Indramayu. One of the reasons is the lack of human resources who understand the ins and outs of Petanque Sports Organizing and Refereeing in Indramayu. As a solution to this problem, Organizational Development and Refereeing activities for Petanque Sports were carried out in Indramayu Regency, West Java Province. The activity was carried out at STKIP NU Indramayu which was attended by 30 participants with various backgrounds such as students, lecturers, trainers and sports teachers. The Instructors camefrom the National and West Java Province Petanque Sport Committee. The activity was carried out for 2 days in the form of Theori and Practice. The result of this activity is the availability of organizational and refereeing human resources who are ready to form the FOPI Branch Committee of Indramayu Regency. Abstrak Kabupaten Indramayu merupakan 4 dari 27 Kabupaten/Kota di Jawa Barat yang belum memiliki Pengurus Cabang Federasi Olahraga Petanque Indonesia (FOPI) sebagai induk cabang olahraga Pembina olahraga Petanque di Indramayu. Salah satu penyebabnya adalah masih kurangnya SDM yang memahami seluk beluk Organisasi dan Perwasitan Olahraga Petanque di Indramayu. Sebagai solusi atas permsalahan tersebut maka dilakukan kegiatan Pengembangan Organisasi dan Perwasitan Cabang Olahraga Petanque di Kabupaten Indramayu Propinsi Jawa Barat. Kegiatan dilaksanakan di STKIP NU Indramayu yang diikuti oleh 30 orang Peserta dengan beragam latar belakang seperti Mahasiswa, Dosen, Pelatih dan Guru Olahraga. Narasumber berasal dari Pengurus PB FOPI dan Pengurus FOPI Propinsi Jawa Barat. Kegiatan dilaksanakan selama 2 hari berupa paparan dan praktek. Hasil dari kegiatan ini adalah tersedianya SDM Organisasi dan Perwasitan yang siap untuk membentuk Pengurus Cabang FOPI Kabupaten Indramayu.